The Greek Orthodox Church in America : A Modern History - Kitroeff, Alexander (Book collections on Project MUSE., 2020)
"Shows how the Greek Orthodox Church became the most important Greek institution in the United States and the main force that shaped Greek American ethnic identity in the twentieth century"--